Biogeography of Micro-Eukaryotic Communities in Sediment of Thermokarst Lakes Are Jointly Controlled by Spatial, Climatic, and Physicochemical Factors Across the Qinghai-Tibet Plateau - Ren, Ze; Zhang, Yitong; Li, Xia; Zhang, Cheng (Frontiers in Ecology and Evolution, 2022)
Thermokarst lakes are formed following ice-rich permafrost thaw and widely distribute in the cold regions with high latitude and elevation. However, the micro-eukaryotic communities (MECs) in thermokarst lakes are not well studied. Employing 18S rRNA gene sequencing, we assessed the biogeography of MECs and their driving factors in sediments of thermokarst lakes across the Qinghai-Tibet Plateau (QTP). Results showed that Diatom, Gastrotricha, Nematozoa, Ciliophora, and Cercozoa were dominant lineages in relative abundance and OTU richness. MECs varied substantially across the lakes in terms of diversity and composition. Structural equation modeling and mantel test showed that both OTU richness and community structure of MECs had close relationships with spatial factors, climatic factors, and sediment properties, particularly with latitude, mean annual precipitation, pH, as well as nutrient concentrations and stoichiometric ratios. Moreover, different groups of microbial eukaryotes (taxonomic groups and co-occurrence modules) responded differentially to the measured environmental variables. The results suggested that the biogeography of sediment MECs of thermokarst lakes on the QTP were jointly controlled by spatial and climatic factors as well as sediment properties. This study provides the first view of the composition, diversity, and underlying drivers of MECs dynamic in surface sediments of thermokarst lakes across the QTP.